(untitled) (Journal of the College of Basic Education, 2023)
Trade is an important source of national income for the residents of Bahrain, due to their location.geographical location in the Arabian Gulf, which facilitated the task of communicating with the rest of the regions of the Arabian Gulf and India.and Southeast Asia from commercial operations importing and exporting the surplus to the markets of Persia and IraqAleppo, Arabia, and Muscat. The profession of diving was to search for pearls in the pools of Bahrain.The profession of their ancestors and their fathers since ancient times, and they used to see it as an important source of their livelihood.It is a difficult profession, but it provides a job opportunity for many job seekers on ships.Diving This trade was not limited to the trade of pearls, but it also extended to other commodities and merchandise.Which had a strong demand in Bahrain and other Arab Gulf regions.It also owned a large commercial fleet operating in the Indian Ocean and the Arabian Gulf.The British authorities attempted to interfere in trade affairs in the Arabian Gulf region in general.Bahrain in particular, in order to preserve its political and economic interests, through a number ofConventions that prohibited the arms and slave trade during the nineteenth century under false pretexts.Trade in Bahrain went through stages of growth and prosperity, then it declined, especially tradePearls, after the discovery of oil and competition with Japanese artificial pearls.trade in Bahrain